Human submandibular-sublingual saliva promotes adhesion of Candida albicans to polymethylmethacrylate. - Edgerton, M (1993)
The purpose of this study was to identify components of saliva that interact with Candida albicans in solution and that may modulate adhesion to dental acrylic (polymethylmethacrylate [PMMA]) surfaces. Saliva-derived pellicles extracted from C. albicans blastoconidia and hyphal-form cells mixed with fresh human submandibular-sublingual saliva (HSMSL) contained predominantly high- and low-molecular-weight mucins (MG1 and MG2, respectively). In contrast, few components from fresh human parotid saliva were adsorbed to yeast cells. Coating PMMA beads with HSMSL significantly enhanced (10-fold) adhesion of both growth forms of C. albicans compared with human parotid saliva (2-fold), suggesting a role for mucins in adhesion. HSMSL-enhanced adhesion was completely abolished by preadsorbing HSMSL with either blastoconidia or hyphal-form cells prior to coating PMMA. However, coating PMMA with purified salivary mucins or the addition of mucin to preadsorbed saliva did not enhance or restore adhesion to levels found with fresh HSMSL. Adhesion assays employing guanidine-treated fresh HSMSL showed a complete lack of Candida binding, suggesting that subjecting HSMSL to dissociating conditions may alter a property of salivary mucins crucial for C. albicans adhesion. Protease and glycosidase treatment of yeast cells significantly reduced adhesion to HSMSL-coated PMMA. In addition, preincubation of C. albicans with mannose and galactose inhibited adhesion to HSMSL-coated PMMA. These results suggest that mucins may play a role in C. albicans adhesion to saliva-coated PMMA and that a glycoprotein on the yeast surface may be involved in these events.